Minimally invasive direct coronary artery bypass graft surgery versus percutaneous coronary intervention of the LAD: costs and long-term outcome. (May 2019) - Merkle, Julia; Zeriouh, Mohamed; Sabashnikov, Anton; Azizov, Farid; Hohmann, Christopher; Weber, Carolyn; Eghbalzadeh, Kaveh; Said, Yousef; Wahlers, Thorsten; Michels, Guido
Objective: Outcomes and treatment costs for coronary artery disease involving the left anterior descending coronary artery (LAD) are influenced by the type of treatment, which can be either isolated minimally invasive revascularization of the LAD using the internal thoracic artery (ITA) (MIDCAB) or percutaneous coronary intervention (PCI) on the LAD. This retrospective study sought to evaluate long-term survival, freedom from re-intervention and cost analysis after MIDCAB compared to PCI on the LAD. Methods: Between 2006 and 2012, from a total of 561 patients, 106 consecutive patients with LAD stenosis underwent a MIDCAB procedure whereas 100 patients underwent elective PCI. Urgent and emergent cases were excluded from the present study (n = 355). Detailed analysis of the outcome data was performed for both groups. A Kaplan–Meier survival estimation with up to 10-year follow-up was applied for both groups for survival analysis and freedom from re-intervention. Results: There were no statistically significant differences in terms of clinically relevant baseline characteristics. The outcome in the MIDCAB group was superior regarding long-term overall survival, accounting for 100% versus 92.8% at 1 year, 98.5% versus 82.1% at 6 years and 79.6% versus 61.5% at 10 years (Log Rank (Mantel-Cox) p = 0.011) and freedom from re-intervention at 10 years (97.2% vs. 86.7%, Log Rank (Mantel-Cox) p = 0.001). Intensive care unit (ICU) stay (p = 0.020) and total hospital stay (p<0.001) were significantly longer in the MIDCAB group, which was also associated with higher in-hospital costs (10, 879 € vs. 4009 €, p<0.001). Conclusions: Whereas patients undergoing MIDCAB remained longer on ICU and in hospital, causing higher costs, this procedure was associated with a significantly lower incidence of repeat revascularization and significantly lower mortality compared to PCI on the LAD.